Β-arrestin expression in corticotroph tumor cells is modulated by glucocorticoids. Issue 1 (April 2020) - Gatto, Federico; Feelders, Richard A; van der Pas, Rob; van Koetsveld, Peter; Bruzzone, Eleonora; Arvigo, Marica; Dogan, Fadime; Lamberts, Steven; Ferone, Diego; Hofland, Leo
Abstract : Pituitary-directed medical treatment for Cushing's disease (CD) is currently represented by membrane receptor targeting drugs (somatostatin analogs and dopamine agonists). Somatostatin and dopamine receptors are regulated by β-arrestins, which have been shown to be differentially regulated by glucocorticoids in non-neuroendocrine cells. In this study we investigated the effects of glucocorticoids on β-arrestin expression in corticotroph tumor cells. First, AtT20 cells, a mouse model of CD, were exposed to dexamethasone (Dex) at different time points and β-arrestin expression was evaluated at mRNA and protein levels. Futhermore, β-arrestin mRNA expression was evaluated in 17 human corticotroph adenoma samples and correlated to patients' pre-operative cortisol levels. We observed that Dex treatment induced a time-dependent increase in β-arrestin 1 mRNA expression and a decrease in β-arrestin 2. The same modulation pattern was observed at protein level. Dex-mediated modulation of β-arrestins was abolished by co-treatment with mifepristone, and Dex withdrawal restored β-arrestin expression to basal levels after 72 h. The evaluation of β-arrestin mRNA in corticotroph adenomas from CD patients with variable disease activity showed a significant positive correlation between β-arrestin 1 mRNA and urinary cortisol levels. The effect of glucocorticoids on β-arrestin levels was confirmed by the analysis of two samples from a single patient, which underwent adenomectomy twice, with different pre-operative cortisol levels. In conclusion, glucocorticoids induce an inverse modulation of the two β-arrestin isofoms in corticotroph tumor cells. Since β-arrestins regulate membrane receptor functions, this finding may help to better understand the variable response to pituitary-targeting drugs in patients with Cushing's disease.